2012
DOI: 10.1155/2012/452541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adjunct Low-Dose Vitamin D on Relapsing-Remitting Multiple Sclerosis Progression: Preliminary Findings of a Randomized Placebo-Controlled Trial

Abstract: The aim of this preliminary study was to evaluate the effect of low-dose oral vitamin D in combination with current disease-modifying therapy on the prevention of progression of relapsing-remitting multiple sclerosis (RRMS). A phase II double-blind placebo-controlled randomized clinical trial conducted between October 2007 and October 2008 included 50 patients with confirmed RRMS aged 25 to 57 years and normal serum 25-hydroxyvitamin D. They were randomly allocated to receive 12 months of treatment with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 29 publications
0
49
0
2
Order By: Relevance
“…The capacity of low dose calcitriol to prevent disease progression in relapsing remitting multiple sclerosis (RRMS) when given in adjunction to undefined disease-modifying treatment strategies was investigated in a randomised and double blind but rather small study on 50 patients. After 12 months, no significant differences between verum and placebo arms were observed with respect to relapse rate and disability [118]. Two recently published studies from Finland and Norway, both applying 20,000 IU/week in a randomised, double blind and placebo-controlled design (evidence level Ib), yielded partly contradictory results with respect to clinical and MRI parameters.…”
Section: Reviewmentioning
confidence: 99%
“…The capacity of low dose calcitriol to prevent disease progression in relapsing remitting multiple sclerosis (RRMS) when given in adjunction to undefined disease-modifying treatment strategies was investigated in a randomised and double blind but rather small study on 50 patients. After 12 months, no significant differences between verum and placebo arms were observed with respect to relapse rate and disability [118]. Two recently published studies from Finland and Norway, both applying 20,000 IU/week in a randomised, double blind and placebo-controlled design (evidence level Ib), yielded partly contradictory results with respect to clinical and MRI parameters.…”
Section: Reviewmentioning
confidence: 99%
“…[2833] (Figure 1) However, the study by Aivo et al[33] was a sub-study of another main trial. [31] Of the five trials included, four gained the maximum score;[2932] one study scored two points (the authors did not mentioned randomization and blinding procedures, as well as the reasons for patient withdrawals and dropouts for each treatment group). [28] The randomization procedure was reported in sufficient detail to be sure that it was appropriate in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…[28] The randomization procedure was reported in sufficient detail to be sure that it was appropriate in four studies. [2932] In one study, the randomization procedure was not reported. [28] Likewise, double blinding method was appropriately explained in four studies;[2932] in one study was nor reported.…”
Section: Resultsmentioning
confidence: 99%
“…A 6-month randomized clinical trial of 300,000 IU vitamin D3 per month, comprising 62 patients treated with IFN-β 1a , did not find any effect on EDSS or gadolinium-enhancing MRI lesions, but an increase in the expression of IL-10 and TGF-β and a reduction in T-cell proliferation [104]. Another-12 month study of 50 RRMS patients, all on immunomodulatory treatment, did not show any effect on relapse rate or EDSS development of escalating doses of calcitriol up to 0.5 mg per day compared with placebo [105]. After adjustment for baseline EDSS, Stein et al reported marginally higher EDSS in 11 patients who had received high-dose (6000 IU) compared with 12 patients who had received low-dose (1000 U) vitamin D 2 , whereas no differences were recorded in the primary MRI end points [13].…”
Section: Clinical Trialsmentioning
confidence: 90%